Genital ulcer, nor always a classic DST: case report of a tuberculosis vulvar - C Filho, Antônio; Rabelo, Priscila C; Martinelli, Thiago; Faria, Carlos de; Rezende, Ricardo B de (Brazilian Journal of Sexually Transmitted Diseases, 2006)
The tuberculosis to vulvar is a rare pathology, generally associated to a pulmonary primary focus. The objective of this ceport is to present the clini-cal, diagnostic picture and treatment of a vulvar tuberculosis followied in the service of Gynecology of the Santa Casa de Misericórdia de Vitória in2004. The case of a patient of 54 years old, married, with a chronic genital ulcer, of great extension, without other symptoms associates. It was sub-mitted the biopsy of the injury and examinations for inquiry of some sexually transmissitted deseases (syphilis, hepatites and HIV). The results thebiopsy it evidenced granuloma suggestive of tuberculosis, after to discard others suspicion. It was become fullfilled x-ray of thorax, which presentedsuggestive injuries of tuberculosis. Baciloscopy of pulmonary secretion became, with positive result. Ahead of the pulmonary picture of tuberculosisand the result found in the biopsy of the genital ulcer, the treatment with tuberculostatics was initiated. Confirmation of the tuberculosis was gottenthen to vulvar through positive the therapeutical test, with significant improvement of the genital injury in first the seven days of treatment. It wasobserved the importance of if having the tuberculosis as diagnostic differential in the chronic genital ulcers, for requiring adequate diagnostic inquiryto do the necessary treatment and getting the cure.